CROSS CULTURAL COMMUNICATION AWARENESS IN TRANSLATION - Havid Ardi (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2015)
A translation is a bridge of communication among nations that have unique cultures and language. In fact, cultural differences lead to different ways of delivering ideas or message. Even, similar utterance might have different meaning depend on its contextual setting and the speaker. Therefore, translation process is not a simple activity of replacing words from a language into another language. This paper aims at introducing cross cultural communication awareness that must be owned to be a professional translator. Besides, this paper also aims at showing the use of pragmatic analysis in understanding and solving the problem of translation related to cultural differences. Firstly, some sources of (unidentified) translation problems related to specific feature of languages are raised and ways to analyze and solve the problems are proposed. Key words: cross cultural, cultural awareness, pragmatic, translation.